Communicating the move towards social entrepreneurship: The role of key partners for women empowerment initiative in East Java - Suko Widodo; Sulikah Asmorowati; Anita Dewi; Calvin Nathan Wijaya; Charisma Husniati (Masyarakat, Kebudayaan dan Politik, 2022)
The empowerment as well as welfare impact of the implementation of the Feminisation of Poverty Alleviation Program (PFK Program) on its beneficiaries – the underprivileged Female Household Heads (KRTPs)- in East Java, can be considered as range from low to moderate. In this, there is a need for furthering the empowerment impact of the program, which can be done, amongst other, through the adoption a social business model, namely Business Model Canvas (BMC). This study aims to examine key partners’ role in supporting the adoption of Business Model Canvas (BMC) elements for a government-initiated entrepreneurship program at the grass-roots level. The study employs qualitative case study research using observation, document analysis and interviews with 98 key partners in four districts (Banyuwangi, Lamongan, Nganjuk, and Trenggalek). The key partners are divided into three categories, namely local governments, KRTPs, and local institutions/communities. The study finds that to further the empowerment impact of the PFK Program, Trenggalek is the readiest among the four districts, followed by Nganjuk, Lamongan, and Banyuwangi, to adopt Business Model Canvas (BMC). It is further argued that the application of Business Model Canvas (BMC) can contributed to an adequate description of key partners’ readiness to support the program by establishing the customer segments, value propositions, channels, revenue streams, customer relationships, key resources, and managing the cost structure that accelerate the role of key partners in moving towards social entrepreneurship.